Reduced HIV-stimulated T-helper cell reactivity in cord blood with short-course antiretroviral treatment for prevention of maternal–infant transmission - Kuhn, L (Blackwell Science Inc, 2001)
T-helper cell responses to HIV have been associated with protection against maternal-infant HIV transmission in the absence of antiretroviral treatment, but the effects of antiretroviral treatment, now widely used for prevention, on development of these cell-mediated responses is unknown. We tested whether development of T-helper cell responses to HIV and other antigens would be affected by exposure to short-course regimens of zidovudine-lamivudine (ZDV-3TC) given to prevent maternal-infant HIV transmission. Cord blood samples were collected from 41 infants of HIV-infected mothers enrolled in a clinical trial in which they were treated with regimens of ZDV-3TC and from 29 infants whose HIV-infected mothers were not treated with any antiretroviral drugs. T-helper cell reactivity to HIV envelope peptides and other antigens was measured in vitro using a sensitive culture supernatant titration assay based on IL-2-dependent proliferation. Infants in the clinical trial were followed to 18 months to determine their HIV infection status, and venous blood samples were re-tested at 4·5 and 9 months for T-cell reactivity to HIV. HIV-stimulated T-helper cell reactivity in cord blood was detected 10-fold less frequently among those exposed to antiretroviral prophylaxis (2·4%) than among those unexposed (24·1%) (P = 0·007). Reductions in HIV-stimulated responses in cord blood occurred despite detectable HIV RNA (mean 3·38 standard deviation 0·76 log(10) copies per ml) at delivery among treated women and occurred independent of treatment duration. Our results suggest that short-course antiretroviral treatment given to prevent maternal-infant HIV transmission may attenuate HIV-stimulated T-cell memory responses in the neonate.